Analisis Kebutuhan Kebijakan Pemerintah Kabupaten dalam Mengimplementasikan Keputusan Mahkamah Konstitusi No. 35/PUU-X/2012 - Andi Massoeang Abdillah; Yusran Jusuf Jusuf; M.Asar Said Mahbub (Fakultas Kehutanan, Universitas Hasanuddin, 2018)
This study aims to : (1)To identify Kajang eligibilities of customary law, based on the law 41 of 1999 (article 67) to be recognized by local authorities as before customaty law determination as indigenous forests. (2)To identify the obstacles in the process of a strengthening the community of Kajang customary law in Bulukumba regency.(3)To formulate policy needed in maintaining the existence of indigenous community and forest conservation. This study was conducted in the village of Tana Toa, Subdistrict of Kajang, Bulukumba, South Sulawesi province. Descriptive analysis was used to determine the condition of Kajang customary law, in accordance with the terms used to confirm customary law communities by the local governments, obstacles in the process of strengthening the customary law community, as well as to describe perceptions of stakeholders in relation with constitutional courts decisions. Policy analysis was used to form policies needed in maintaining the existence of indigenous communities and forest conservation. The results of the study showed that Kajang customary law qualified and has been confirmed as customary law communities. The form of policies needed were policies that could synergize government and customary law in managing and conserving forests, proportional policies and necessary technical policies that could regulate the management and procurement of forest resources by Kajang customary law community. The perception of stakeholders were varied, but all supporting the indigenous forests to be passed through local legislation. On the other hand the stakeholders expected the government could assist in the process and remain as a driver and controller of customary law communities in the management of forest resources.